In-Silico Investigation of Compounds from Black Mangrove (Rhizophora mucronata L.) as Inhibitors of Exo-1,3-β-Glucanase in Candida albicans - Ririn Puspadewi; Dadan Suryasaputra; Rizki Nurrohmana (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Candida albicans is an opportunistic fungal pathogen responsible for systemic infections that result in considerable morbidity and mortality. The enzyme Exo-1,3 β-glucanase is essential for cell wall metabolism and pathogenicity in C. albicans, rendering it a potential therapeutic target. The study aims to evaluate the effectiveness of bioactive compounds from black mangroves (Rhizophora mucronata L.) as inhibitors of Exo-1,3 β-glucanase using an in silico approach. The test results from 28 black mangrove plant compounds yielded a the free energy value (ΔG) with a the inhibition constant (KI) comparable to that of ibrexafungerp. The four compounds exhibited the following properties: β-amyrin (ΔG) = -8.24 kcal/mol with KI = 908.46 nM, lupeol = -8.19 kcal/mol with KI = 994.44 nM, ethyl-iso allocholate = -7.66 kcal/mol with KI = 2.44 μM, and magnolol = -7.2 kcal/mol with KI = 5.25 μM. The molecular docking test results were evaluated from multiple perspectives, specifically the ΔG value generated post-docking, the KI, and the interactions of amino acid bonds and residues with the receptor. The ADMET prediction test results indicate that the four molecular docking test chemicals exhibit commendable skin penetrating capabilities. Based on the results of the tests, the four compounds, namely Ethyl-isoallocholate, β-amyrin, Magnolol, and Lupeol with β-amyrin, have the potential to become new drug candidates as Exo 1-3-(-glucanase inhibitors) in Candida albicans